hetL Overexpression Stimulates Heterocyst Formation in Anabaena sp. Strain PCC 7120 - Liu, Duan (American Society for Microbiology, 2002)
The cyanobacterium Anabaena sp. strain PCC 7120 forms single heterocysts about every 10 to 15 vegetative cells along filaments. PatS is thought to be a peptide intercellular signal made by developing heterocysts that prevents neighboring cells from differentiating. Overexpression of the patS gene suppresses heterocyst formation. The hetL gene (all3740) was isolated in a genetic screen to identify genes involved in PatS signaling. Extracopy hetL allowed heterocyst formation in a patS overexpression strain. hetL overexpression from a heterologous promoter in wild-type Anabaena PCC 7120 induced multiple-contiguous heterocysts (Mch) in nitrate-containing medium. The predicted HetL protein is composed almost entirely of pentapeptide repeats with a consensus of A(D/N)L*X, where * is a polar amino acid. Thirty Anabaena PCC 7120 genes contain this repeat motif. A synthetic pentapeptide corresponding to the last 5 amino acids of PatS, which suppresses heterocyst formation in the wild type, did not suppress heterocyst formation in a hetL overexpression strain, indicating that HetL overexpression is affecting heterocyst regulation downstream of PatS production. The transcription regulator NtcA is required for the initiation of heterocyst formation. hetL overexpression allowed the initiation of heterocyst development in an ntcA-null mutant, but differentiation was incomplete. hetR and hetC mutations that block heterocyst development are epistatic to hetL overexpression. A hetL-null mutant showed normal heterocyst development and diazotrophic growth, which could indicate that it is not normally involved in regulating development, that it normally plays a nonessential accessory role, or perhaps that its loss is compensated by cross talk or redundancy with other pentapeptide repeat proteins.